Muketing: the fusion of Mutelu and marketing in e-commerce—trends in Thailand’s faith economy - Limna, Pongsakorn; Shaengchart, Yarnaphat; Kraiwanit, Tanpat; Asanprakit, Saranchana; Nivornusit, Rattawut (Frontiers in Communication, 2025)
BackgroundThe intersection of traditional spiritual beliefs and digital commerce is reshaping consumer behavior in Thailand. Muketing—a blend of Mutelu spirituality and modern marketing—has emerged as a distinct cultural-marketing phenomenon within the country’s expanding faith economy. This study explores the emerging phenomenon of Muketing within Thailand’s e-commerce sector.MethodsThis study employed a qualitative research design using in-depth interviews with twelve Thai consumers who actively engage in online shopping through e-commerce platforms. Content analysis was conducted to identify key themes related to consumer attitudes, trust, engagement, and purchasing behaviors.ResultsThe findings reveal that Muketing enhances consumer attitudes through emotional and cultural relevance, fosters trust via perceived authenticity and spiritual alignment, and boosts engagement through interactive and symbolic content. Participants reported increased purchase intentions when products incorporated rituals, spiritual messaging, or symbolic imagery tied to traditional beliefs.ConclusionThe study demonstrates that Muketing influences purchasing behavior within the study’s sample by integrating local belief systems with modern marketing practices, thereby fostering culturally resonant consumer bonds. When practiced authentically and ethically, spiritual branding can generate meaningful commercial outcomes. Further research is needed to examine its underlying mechanisms and assess its broader applicability across diverse contexts and consumer groups.